Integrasi Logika-Ilmiah dan Mistis-Spiritual Melalui Pendekatan Metafisika Eksakta dan Psikologi Transpersonal - Muhammad Briliant Syah; Konto Iskandar Dinata (Al-Kindi, 2025)
This study explores the paradigmatic integration of scientific logic and mystical-spiritual experience through exact metaphysics and transpersonal psychology within the framework of Sufism, departing from modern anxieties when religion is trapped in dogmatism and positivist science reduces reality. Using a qualitative approach based on literature review and comparative-interpretive analysis, the study focuses on Robert Frager's "Sufi Psychology" on the evolution of the seven levels of the nafs (self-centeredness) and Sheikh Kadirun Yahya's "Capita Selecta Agama, Metaphysics, and Exact Reality," which interprets spiritual reality in the language of energy and exact laws. The findings demonstrate that exact metaphysics can demythologize spiritual experience without reducing its depth, while transpersonal psychology parallels the process of tazkiyatun nafs (self-centeredness). The integration of the two produces a holistic model that unites the psychological and spiritual dimensions and finds its actualization in the Naqshbandiyah Khalidiyah Order as a contemporary spiritual laboratory. This research ultimately offers a re-enchantment project that presents a rational yet non-reductive spirituality, while also providing a theoretical framework and practical roadmap for the journey toward becoming a perfect human being in the modern era